AB1047 Evidence that a systemic predisposition to chondrocalcinosis exists, and is mediated by osteoarthritis at most but not all joints. (23rd January 2014) - Abhishek, A.; Doherty, S.; Maciewicz, R.; Muir, K.; Zhang, W.; Doherty, M.
Abstract : Background: It is not known whether radiographic chondrocalcinosis (CC) results from a systemic predisposition or whether the association between CC and osteoarthritis (OA) is joint specific or generalized. Objectives: To ascertain if there is a systemic predisposition to CC, and to examine if the association between CC and OA is joint specific or systemic. Methods: A cross-sectional study embedded in GOAL – the Genetics of Osteoarthritis and Lifestyle study (n=3, 170). All participants in GOAL have radiographs of knees, hands, and pelvis, and these have been scored for changes of osteoarthritis (OA), and for the presence of CC. The risk of CC at each joint was estimated and compared according to CC in the distant joint, as well as OA at the same and distant joints. Odds ratio (OR) and 95% confidence interval (CI) was used to measure the association. The OR was adjusted for age, gender, body mass index (BMI), and OA at the distant joints (aOR). OA was defined if the Kellgren and Lawrence score was ≥2 at either hips, ≥3 at either knees, and there was definite joint space narrowing at either wrist. Results: CC at one joint is associated with CC at other joints. This association was observed in knees, hips, wrists, metacarpophalangeal joints (MCPJs), and symphysis pubis (Table 1). CC was associated with OA at the same knee, wrist and MCPJ. The aOR (95%CI) ranged from 2.20 (1.62-2.99) to 5.58 (2.72-11.47). However, there was no association between CC and OA at the same hip (aOR 1.05, 95%CI 0.72-1.55 right, and 0.68, 0.41-1.13 left hip). While knee OA associated with CC at all distant joints, hip OA did not associate with CC at any of the distant joints. Conclusions: CC occurs at least in part due to a systemic predisposition, some of which is mediated by OA. While there is evidence to suggest that OA associates with CC due to a generalised predisposition, this varies according to the joint affected by OA – the predisposition being present for knee OA and not for hip OA. Disclosure of Interest: None Declared.